1998
DOI: 10.1103/physreve.57.3115
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic behavior of an ordering latex suspension in a steady shear flow

Abstract: The linear viscoelastic behavior of an ordering polystyrene latex during steady shear flow has been investigated. In this study a home-made instrument has been used that superimposes a small-amplitude oscillatory shear orthogonal onto the steady shear flow. The measurements can be interpreted as due to the coexistence of two phases under flow. For increasing shear rate the ordered ͑or solidlike͒ phase melts away until the suspension becomes completely disordered ͑or fluidlike͒. A model is presented in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On the other hand, the change of system ͑ii͒ into system ͑iii͒ represents the coalescence of crystallites and one observes that coalescence results in an increase of GЈ for low frequencies ͑while it remains constant for intermediate and high frequencies͒ and it results in an increase of GЉ for low frequencies and a decrease of GЉ for intermediate and high frequencies. We have already noted that the measurements carried out by Van der Vorst et al 55 showed an increase of GЈ and a decrease of GЉ as a function of the preshear time. Thus, the growing and alignment of the crystallites due to preshearing is reflected by the increase of GЈ(), while the coalescence of crystallites is reflected by the decrease of GЉ()Ϫ ϱ .…”
Section: The Dependency Of the Dynamic Moduli On Preshearmentioning
confidence: 81%
See 4 more Smart Citations
“…On the other hand, the change of system ͑ii͒ into system ͑iii͒ represents the coalescence of crystallites and one observes that coalescence results in an increase of GЈ for low frequencies ͑while it remains constant for intermediate and high frequencies͒ and it results in an increase of GЉ for low frequencies and a decrease of GЉ for intermediate and high frequencies. We have already noted that the measurements carried out by Van der Vorst et al 55 showed an increase of GЈ and a decrease of GЉ as a function of the preshear time. Thus, the growing and alignment of the crystallites due to preshearing is reflected by the increase of GЈ(), while the coalescence of crystallites is reflected by the decrease of GЉ()Ϫ ϱ .…”
Section: The Dependency Of the Dynamic Moduli On Preshearmentioning
confidence: 81%
“…In Van der Vorst et al 55 measurements are given of the dynamic moduli GЈ() and GЉ() as a function of the preshear time, i.e., the duration of the applied preshear was 0, 4, 6, 10, and 36 min. These experiments show that preshearing of a colloidal crystal results in an enhanced ͑long range͒ ordering in the sample, i.e., it was observed that due to the preshearing the storage modulus GЈ() was increasing, while, simultaneously, the loss modulus GЉ() was decreasing.…”
Section: The Dependency Of the Dynamic Moduli On Preshearmentioning
confidence: 99%
See 3 more Smart Citations